The problems of Mu’allaf in Malaysia - Mohd Syukri Yeoh Abdullah; Osman Abdullah @ Chuah Hock Leng (Penerbit Universiti Kebangsaan Malaysia, 2003)
It is almost a common knowledge in Malaysia that the Muslims, normally referred to as ‘Muslim converts’, are facing a dilemma resulting in them not becoming practicing Muslims. In the majority of cases, this phenomenon does not suggest a lack of conviction or wrong intention at the time when they accepted Islam, but because they have absolutely no access to proper and continuous guidance to enable them to deepen their knowledge of Islam. Most of them, after they have embraced Islam, continue to exist, as before, not giving adequate attention to the Islamic way of life. Some of these new Muslims in Malaysia revert to their previous religions. The Muslims in Malaysia as a whole, the Pusat Islam Malaysia, the Non-Governmental Organizations, the Muslims individually and collectively could perhaps contribute in an effort to seek a way to save them and change the situation. The problems confronting new Muslims in Malaysia appear to have no immediate resolution, unless there emerges a way of thinking which may help them to rediscover the knowledge together with the will to form a unique community, having the necessary qualities of primal Islam of the first community of al-Medina al-Munawwara